Review of The Development of Extreme Sports (Skateboarding) in Subang Regency - Muhammad Iqbal; Vicki Ahmad Karisman; Dedi Kurnia (Journal of Physical and Outdoor Education, 2026)
This study aims to review the development of extreme sports, specifically skateboarding, in Subang Regency using a phenomenological approach. Skateboarding, as one of the extreme sports branches increasingly favored by the youth in Subang, shows significant growth despite facing various challenges such as limited facilities and insufficient government support. This research examines the role of the skateboarding community in enhancing public interest and participation, as well as the local government's support for the sport's development. Data were collected through observations and interviews with the skateboarding community, local government officials, and the general public. The results indicate that the skateboarding community actively promotes the sport through various activities and events, yet government support needs to be improved, particularly in providing facilities and structured training programs. This study recommends strengthening the synergy between the community and government to support the advancement of skateboarding in Subang Regency, enabling it to become a sport that contributes to recreational and competitive sports development in the region.